A semiotic analysis of local interior design magazines on the image of the interior design practice in the Philippines - Ryser, Grace V.
This study examined how local interior design magazines contribute in reinforcing the existing social constructs of the interior design profession and professionals. These social constructs were: 1) interior design is inferior to architecture; 2) interior design is a female domain; 3) interior design is expensive and extravagant; 4) anyone can be an interior designer and; 5) interior designers are shown as glamorous people rather than a serious professional. The sampling frame of this study included one current issue and two back issues, totaling to three issues each, of Real Living, My Home, and Metro Home magazines. A quantitative content analysis was first used to produce data that served as signifiers to the semiotic analysis. A semiotic analysis was then conducted using Pierce's framework in interpreting signs, and Kress and van Leeuwen's framework in making meanings out of visual images. According to the results, all social constructs were presented to be true. Interior design's inferiority with architecture was not dramatically significant and varied according to the time frame of the issues. The profession was portrayed mostly as a female domain and associated with higher socioeconomic class. Undermining of the professional status of interior design was observed, but was not vividly evident. The conceptual image that was formed of interior designers is that they are young, glamorous, fashionable, artistic, indulgent, and carefree individuals. Their images possessed a strong viewer involvement, and their composition has a high modality. The study concluded that these interior design magazines do reflect the social constructs of the interior design profession. The study recommends parallel studies about local interior design magazines in relation to public perception, or professional interior design practice.